2019
DOI: 10.35188/unu-wider/2019/724-8
|View full text |Cite
|
Sign up to set email alerts
|

Educational mobility in developing countries

Abstract: provides economic analysis and policy advice with the aim of promoting sustainable and equitable development. The Institute began operations in 1985 in Helsinki, Finland, as the first research and training centre of the United Nations University. Today it is a unique blend of think tank, research institute, and UN agency-providing a range of services from policy advice to governments as well as freely available original research. The Institute is funded through income from an endowment fund with additional con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 112 publications
1
28
0
Order By: Relevance
“…This finding is consistent with a previous study where it is reported that literate parents are more likely to send their children to school in Bangladesh [47,48]. Moreover, in developing countries, children's educational attainment is more positively correlated with their parent's education [48,49]. Evidence also shows that the likelihood of a higher educated father will have a higher educated child is higher because higher educated fathers are financially rich and they make enormous efforts to confirm their children's academic success [50,51].…”
Section: Plos Onesupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is consistent with a previous study where it is reported that literate parents are more likely to send their children to school in Bangladesh [47,48]. Moreover, in developing countries, children's educational attainment is more positively correlated with their parent's education [48,49]. Evidence also shows that the likelihood of a higher educated father will have a higher educated child is higher because higher educated fathers are financially rich and they make enormous efforts to confirm their children's academic success [50,51].…”
Section: Plos Onesupporting
confidence: 92%
“…considered to carry the name and family title of father and will assure parent's future [49]. In contrast, it is a general practice in rural households not to send their young daughters to schools for higher education as they believe females are born to specially run households [50].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The main attraction of Equations (3) and (4) for developing country settings is that information about intergenerational educational or occupational attainment can be discerned from easy to implement retrospective questions in nationally representative household surveys. This ensures fewer and less severe quality and methodological concerns than data on earnings (Blanden 2013;Emran et al 2017;Torche 2019). It is thus no coincidence that studies of intergenerational mobility in Latin America have relied extensively on retrospective survey questions (Torche 2014: 625).…”
Section: Origin-independence (Persistence) Measures Of Intergeneratiomentioning
confidence: 99%
“…First, it adds to the literature about intergenerational mobility in general (see Black & Devereux, 2011, for a suvey) but specifically to the literature focusing on the geography of socioeconomic mobility that recently received more attention in part because of the work of Chetty et al (2014), which shows important variation across commuting zones in the US. Furthermore, it adds to the recent wave of research that looks at intergenerational mobility in education (see Torche, 2019, for a survey). This set of papers include on one hand those that use household survey data.…”
Section: Introductionmentioning
confidence: 99%